2015
DOI: 10.1007/s10461-015-1140-9
|View full text |Cite
|
Sign up to set email alerts
|

High Burden of HIV Infection and Risk Behaviors Among Female Sex Workers in Three Main Urban Areas of Mozambique

Abstract: This is the first integrated biological and behavioral survey among female sex workers (FSW) in Mozambique. Using respondent-driven sampling, 400, 411 and 429 FSW were enrolled respectively in Maputo, Beira and Nampula in 2011-2012. Estimates were produced using RDSAT 7.1. HIV prevalence was 31.2%, 23.6%, and 17.8% in each location respectively. Among HIV-positive FSW, 48.1%, 79.8% and 89.6% in each city, were unaware of their serostatus. Condom use at last sex with a client was 85.8%, 73.4% and 62.8% among FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…The study is part of the first round of Integrated Biological and Behavioral Surveillance surveys conducted in Mozambique among key populations at higher risk for HIV [2325]. Consistent with published literature on LDTD in Southern, Eastern, and West Africa, we found that substantial numbers of Mozambican LDTD were involved in risky behaviors such as casual partners, sex with sex workers, unprotected sex with both casual and transactional partners and probable alcohol abuse (as measured by AUDIT-C) [5, 7, 10, 12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…The study is part of the first round of Integrated Biological and Behavioral Surveillance surveys conducted in Mozambique among key populations at higher risk for HIV [2325]. Consistent with published literature on LDTD in Southern, Eastern, and West Africa, we found that substantial numbers of Mozambican LDTD were involved in risky behaviors such as casual partners, sex with sex workers, unprotected sex with both casual and transactional partners and probable alcohol abuse (as measured by AUDIT-C) [5, 7, 10, 12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…The rst round of BBS surveys in Mozambique were implemented between 2011-2014 in the country's major urban areas from the three regions: Maputo (MSM, FSW, PWID), Beira (MSM, FSW), Nampula (FSW) and Nampula/Nacala (MSM, PWID). Sampling was done using respondent-driven sampling (RDS), a quasi-probability-based peer-to-peer sampling strategy successfully used to recruit high-risk and hidden populations, whereby participants recruit their peers who meet the enrollment criteria; more information about the survey methodology has been previously published (13)(14)(15).…”
Section: Survey Designmentioning
confidence: 99%
“…Despite this worrying situation, Mozambique does not have a comprehensive strategy to address HIV prevention among young people, although a strategy is being developed addressing school health (10). The National Strategic Plan in Response to HIV/AIDS 2014-2019/2020 identi es adolescent girls and young women (aged [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and their partners, as a priority population, however no policy documents speci cally mention the particular vulnerabilities of young KP (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Results were also shared with other government institutions, such as Mozambique's National AIDS Council (Conselho Nacional de Combate ao HIV/SIDA) and the National HIV/STI Control Program. Findings have also been disseminated at local, national, and international scienti c conferences through poster and oral presentations (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Although communicating ndings to the government, donors, and service delivery partners has been successful, and despite strong collaborations with central-level civil society organizations, sharing results with large numbers of key populations -especially subgroups within these key populations throughout the country (ex: high-income FSW, PWID and MSM or married MSM who may be stigmatized in their communities by their sexual behaviors) -has been a challenge due to the lack of formal networks and community organizations, especially outside of urban centers.…”
Section: Data Use and Disseminationmentioning
confidence: 99%